Spinocerebellar ataxias masquerading as movement disorders: clinical and genetic characterization - Wei, Shanshan; Zhao, Zhe; Li, Nan; Guo, Xuan; Chen, Jiannan; Hu, Jing (Frontiers in Neurology, 2025)
BackgroundSpinocerebellar ataxias (SCAs) exhibit substantial clinical and genetic heterogeneity. SCAs primarily present with progressive ataxia as the cardinal clinical feature. However, they may co-occur with non-ataxic motor symptoms, including various movement disorders. Notably, certain SCA subtypes may present with movement disorders as their primary manifestation. This phenotypic complexity poses significant diagnostic challenges, particularly in distinguishing SCAs from other neurodegenerative conditions with overlapping presentations.MethodsThis study enrolled 35 probands initially diagnosed with movement disorders. Participants were stratified into hypokinetic movement disorders and hyperkinetic movement disorders groups. After excluding known genetic causes of movement disorders through targeted next-generation sequencing (NGS) panel, negative cases received SCA repeat expansion testing. Genetically confirmed SCA cases received comprehensive clinical-genetic characterization.ResultsFour SCA cases were identified in the hypokinetic movement disorders group (n = 28), accounting for 14.29% (4/28). Notably, an SCA8-associated familial parkinsonism pedigree manifested a novel clinical constellation: Parkinson’s disease -like phenotype with spastic paraplegia and levodopa responsive parkinsonism with dystonia. Additionally, we observed: (i) An SCA2 pedigree demonstrating intrafamilial phenotypic heterogeneity; (ii) Two sporadic early-onset parkinsonism cases harboring pathogenic expansions in SCA8 (CTA/CTG 55 repeats) and SCA3, respectively. Two SCA cases were detected in the hyperkinetic movement disorders group (n = 7), representing 28.57% (2/7). We observed: (i) an SCA3 preataxic carrier presenting with Tourette syndrome; (ii) an SCA17 case (CAG/CAA 41 repeats) manifesting dystonia and spastic paraplegia.ConclusionWe characterized a novel clinical constellation in an SCA8-associated familial parkinsonism pedigree: Parkinson’s disease -like phenotype with spastic paraplegia and levodopa responsive parkinsonism with dystonia. We report the first documented occurrence of Tourette syndrome in the pre-ataxic stage of SCA3, though it is more likely a coincidental comorbidity independent of SCA3 progression. Furthermore, our findings indicate that SCA subtypes presenting with movement disorder-dominant phenotypes are likely underestimated in clinical practice.